1999
DOI: 10.1097/00001573-199903000-00003
|View full text |Cite
|
Sign up to set email alerts
|

Acceptance and versatility of the Ross procedure

Abstract: During the 31 years since the initial Ross procedure, data have been collected that have been helpful in assessing long-term performance of the autograft. The ongoing study of the pulmonary autograft supports the use of the Ross procedure in young patients, in females of childbearing age, and in patients with congenital aortic stenosis and complex left ventricular outflow tract obstruction. We continue to see little or no thromboembolism despite no anticoagulation therapy. The remarkable ability of the autogra… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
10
0

Year Published

2001
2001
2009
2009

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 11 publications
(10 citation statements)
references
References 10 publications
0
10
0
Order By: Relevance
“…There was evidence and conviction that the initial inaugurated subcoronary implantation technique has higher early and midterm failure rates when adopted and practiced by many surgeons, each with an individual learning curve. 15 The long-term fate of the pulmonary autograft when used as a free-standing root or inclusion cylinder is largely unknown, particularly in adult patients. A progressive dilatation of the native aorta adjacent to the pulmonary autograft (anastomosis site) may result in neoaortic regurgitation.…”
Section: I-508 Circulation July 4 2006mentioning
confidence: 99%
“…There was evidence and conviction that the initial inaugurated subcoronary implantation technique has higher early and midterm failure rates when adopted and practiced by many surgeons, each with an individual learning curve. 15 The long-term fate of the pulmonary autograft when used as a free-standing root or inclusion cylinder is largely unknown, particularly in adult patients. A progressive dilatation of the native aorta adjacent to the pulmonary autograft (anastomosis site) may result in neoaortic regurgitation.…”
Section: I-508 Circulation July 4 2006mentioning
confidence: 99%
“…Chambers et al and Stelzer et al have also reported an incidence of 12/131 (9%) and 11/145 (7%), respectively [15,18]. This is in contrast to other series where the pulmonary autograft has been used successfully in the management of aortic endocarditis [4,8,19,20,22]. We have had three definite episode of endocarditis in 2 patients (3%) and in both these patients the pulmonary homograft was the initial valve to be affected.…”
Section: Discussionmentioning
confidence: 66%
“…Dilatation of the aortic annulus or the sino-tubular junction causes AI [22]. Dilatation of the sinuses without dilatation of the annulus or the sino-tubular junction does not cause AI though dimensions .…”
Section: Discussionmentioning
confidence: 95%
“…Advocates of the procedure cite the avoidance of anticoagulation and additional surgery as significant advantages over the use of mechanical and bioprosthetic valve replacements, particularly in respect to childbearing potential. 1,2 The aortic valve graft, being autologous tissue, grows along with the patient, 3 but the cadaveric homograft does not; critics thus point to the genesis of pulmonary valve disease in addition to extant aortic valve disease as both an ethical and a practical objection to the procedure. 1,2 Nonetheless, long-term results of the Ross procedure compare favourably to both mechanical and bioprosthetic valves in terms of outcomes and overall cost.…”
Section: Introductionmentioning
confidence: 99%
“…1,2 The aortic valve graft, being autologous tissue, grows along with the patient, 3 but the cadaveric homograft does not; critics thus point to the genesis of pulmonary valve disease in addition to extant aortic valve disease as both an ethical and a practical objection to the procedure. 1,2 Nonetheless, long-term results of the Ross procedure compare favourably to both mechanical and bioprosthetic valves in terms of outcomes and overall cost. [3][4][5][6] The pulmonary valve offers the closest haemodynamic and functional match to a normal aortic valve 1,7 and the Ross procedure is now considered the repair of choice in children and females of childbearing age.…”
Section: Introductionmentioning
confidence: 99%